Development of calcium-permeable AMPA receptors and their correlation with NMDA receptors in fast-spiking interneurons of rat prefrontal cortex - Wang, Huai-Xing (Blackwell Science Inc, 2010)
Abnormal influx of Ca(2+) is thought to contribute to the neuronal injury associated with a number of brain disorders, and Ca(2+)-permeable AMPA receptors (CP-AMPARs) play a critical role in the pathological process. Despite the apparent vulnerability of fast-spiking (FS) interneurons in neurological disorders, little is known about the CP-AMPARs expressed by functionally identified FS interneurons in the developing prefrontal cortex (PFC). We investigated the development of inwardly rectifying AMPA receptor-mediated currents and their correlation with NMDA receptor-mediated currents in FS interneurons in the rat PFC. We found that 78% of the FS interneurons expressed a low rectification index, presumably Ca(2+)-permeable AMPARs, with only 22% exhibiting AMPARs with a high rectification index, probably Ca(2+) impermeable (CI). FS interneurons with CP-AMPARs exhibited properties distinct from those expressing CI-AMPARs, although both displayed similar morphologies, passive membrane properties and AMPA currents at resting membrane potentials. The AMPA receptors also exhibited dramatic changes during cortical development with significantly more FS interneurons with CP-AMPARs and a clearly decreased rectification index during adolescence. In addition, FS interneurons with CP-AMPARs exhibited few or no NMDA currents, distinct frequency-dependent synaptic facilitation, and protracted maturation in short-term plasticity. These data suggest that CP-AMPARs in FS interneurons may play a critical role in neuronal integration and that their characteristic properties may make these cells particularly vulnerable to disruptive influences in the PFC, thus contributing to the onset of many psychiatric disorders.